2013
DOI: 10.1097/ta.0b013e318299616a
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury–induced alterations in peripheral immunity

Abstract: Background The complex alterations that occur in peripheral immunity after traumatic brain injury (TBI) have been poorly characterized to date. The purpose of this study was to determine the temporal changes in the peripheral immune response after TBI in a murine model of closed head injury. Methods C57Bl/6 mice underwent closed head injury via a weight drop technique (n=5) vs. sham injury (n=3) per time point. Blood, spleen, and thymus were collected and immune phenotype, cytokine expression, and antibody p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 36 publications
(36 reference statements)
9
72
0
Order By: Relevance
“…However, it was thought that severe TBI has no influence on the biology of B cells, based on the evidence provided by several studies indicating that the number and frequency of B cells does not change after injury [8, 34, 36]. Consistent with these reports, our study showed that aTBI induced a decrease in CD3 + and CD8 + T cells, but not in CD19 + B cells.…”
Section: Discussionsupporting
confidence: 82%
“…However, it was thought that severe TBI has no influence on the biology of B cells, based on the evidence provided by several studies indicating that the number and frequency of B cells does not change after injury [8, 34, 36]. Consistent with these reports, our study showed that aTBI induced a decrease in CD3 + and CD8 + T cells, but not in CD19 + B cells.…”
Section: Discussionsupporting
confidence: 82%
“…L or R indicate left or right subregion, respectively. Hipp = Hippocampus, Amy = Amygdala, AC = Anterior cortex, PC = Posterior cortex has also been reported in a mouse model of closed head injury using a standardized weight-drop technique [45]. The lack of inflammation observed in our animals indicates that low-energy blast exposures (74.5 kPa) are not always sufficient to sustain chronic neuroinflammation.…”
Section: Discussionmentioning
confidence: 53%
“…An increase in circulating splenic lymphocytes (due to mobilization of immune cells) occurs that is associated with a compromised BBB and the development of splenic atrophy early after experimental TBI 153 , and beyond 30 days after TBI, a decrease in F4/80 + macrophages in the red pulpa and of Ly6C lo tissue macrophages has been observed 154 . TBI is also associated with a loss of thymus mass as a result of a reduction in lineage marker-negative populations and mature T cells that is associated overall with immunosuppressive features 154 .…”
Section: Cerebral and Extracerebral Challenges To The Innate Immune Smentioning
confidence: 99%
“…TBI is also associated with a loss of thymus mass as a result of a reduction in lineage marker-negative populations and mature T cells that is associated overall with immunosuppressive features 154 .…”
Section: Cerebral and Extracerebral Challenges To The Innate Immune Smentioning
confidence: 99%